The Comparison of the Parameters Antioxidant Activity of Ginger (Zingiber officinale Roscoe) and Commercial Antioxidants - Harliansyah; Kuslestari (International Journal of Science and Society, 2022)
The study was aimed at evaluating the antioxidant activity of Zingiber officinale Roscoe (ginger) extract compared to antioxidant compounds such as; Butyl Hydroxy toluene (BHT), Diethyl-dithiocarbamate (DDC) and Ascorbic Acid (Vit. C). The antioxidant activity (DPPH), total phenolic content (TPC) and reducing power (RP) were studied. DPPH inhibitory values demonstrated through IC50 from ginger extract were significantly lower than those of other antioxidants at the same concentrations: ginger (122.2 ± 16.78%), Vit. C (158.21 ± 4.14%), BHT (195.84 ± 5.94%) and DDC (240.39 ± 43.75%) respectively. This proves that ginger extract is more active inhibiting DPPH free radicals. At a concentration of 100 μg / ml, the TPC level indicates the order: Vit. C > DDC > BHT > ginger respectively. As for RP test at concentration 100 μg / ml also Vit. C > ginger > DDC > BHT respectively. The results obtained in present study indicate that, ginger extract is a potential source of natural antioxidant capable of inhibiting and breaking the free radical chain and it’s expected to suppress the development of degenerative cells diseases.